Properties, Genesis and Classification of Soils on Volcanic Materials in Lembang Area, West Java, Indonesia - Garyanti, Edi Yatno (2003)
Soils developed on volcanic materials have high potential for agricultural production. However, the productivity of some of them is below their potential capacity. Proper management of these soils must be based on understanding their nature and properties. Lembang is one of the most intensively cultivated areas for horticultural crops, tea and pine trees in West Java, Indonesia. Unfortunately, data on the characteristics of soils developed on different volcanic materials of different ages in this area are still limited. Thus, six representative soil profiles developed on andesitic volcanic ash and tuff were studied. The objectives of this study were to determine the soil physical, chemical, mineralogical and micromorphological properties, to relate the soil properties to soil-forming processes and to classify the soils according to Soil Taxonomy and World Reference Base. The results of this study show that all the soils have very deep solum (>1 50 em). Some soil profiles developed on volcanic ash have buried organic-rich horizons as a result of repeated thin ash deposition. In general, the volcanic ash soils are darker coloured, more granular, more friable, less sticky and less plastic than the volcanic tuff soils. The ash soils generally have silt loam to clay loam textures, while the tuff soils have clay texture. The ash soils have lower bulk density (0.38 to 0.79 Mglm\ higher total porosity (55 to 84%) and higher available water content ( 1 3.0 to 34.6%) than the tuff soils. The pH H20 of the soils ranges from 3.52 to 5 .88. Some soil profiles in both parent materials show high exchangeable Al (2.2 to 5.9 cmolc/kg). The ash soils have higher pHNaF (> 9.4), higher organic carbon (up to 1 0%), and higher phosphate retention (> 85%) than the tuff soils. The high values of pHNaF and phosphate retention in the volcanic ash soils are related to the presence of large amounts of amorphous AI. The CEC is generally higher in the ash soils (22 to 46 cmolc/kg) than in the tuff soils ( 1 8 to 3 1 cmolclkg). The base saturation is generally low « 1 5%) in the upper horizons of all the soils. The sand fractions of the ash soils are dominated by hornblende, while the tuff soils are predominantly composed of opaque minerals or magnetite .. In the silt fractions, all the soils in both parent materials show traces to minor amounts of cristobalite, tridymite and quartz. Gibbsite is only observed in the loamy tuff profile, while hydrated halloysite is only present in the lower horizons of another tuff profile. In the clay fractions, the ash soils are dominated by allophane with varying amounts of cristobalite, whereas the tuff soils show a high content of gibbsite and metahalloysite.